2005
DOI: 10.1038/labinvest.3700349
|View full text |Cite
|
Sign up to set email alerts
|

Role for Hedgehog signaling in hepatic stellate cell activation and viability

Abstract: Hepatic stellate cells (HSC) have a complex phenotype that includes both neural and myofibroblastic features. The Hedgehog (Hh) pathway has been shown to direct the fate of neural and myofibroblastic cells during embryogenesis and during tissue remodeling in adults. Therefore, we hypothesized that Hh signaling may regulate the fate of HSC in adults. In this study, we find that freshly isolated stellate cells from adult PatchedlacZ transgenic mice exhibit b-galactosidase activity, indicating Hh pathway activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 69 publications
8
150
2
Order By: Relevance
“…Adding Shh neutralizing antibodies to primary rat HSC increased their inherent caspase activity. These findings extend and confirm data derived from earlier studies of clonal HSC lines, in which Shh antibodies increased cellular apoptosis and recombinant Shh stimulated growth [29]. The present study also demonstrates that proliferative actions of PDGF-BB, a major HSC mitogen [45,46], are mediated via the Hh pathway because three distinct approaches that abrogate Hh signaling each significantly inhibited PDGF-related increases in HSC incorporation of BrdU.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Adding Shh neutralizing antibodies to primary rat HSC increased their inherent caspase activity. These findings extend and confirm data derived from earlier studies of clonal HSC lines, in which Shh antibodies increased cellular apoptosis and recombinant Shh stimulated growth [29]. The present study also demonstrates that proliferative actions of PDGF-BB, a major HSC mitogen [45,46], are mediated via the Hh pathway because three distinct approaches that abrogate Hh signaling each significantly inhibited PDGF-related increases in HSC incorporation of BrdU.…”
Section: Discussionsupporting
confidence: 91%
“…Although Hh ligands are not known to regulate liver development during embryogenesis [24], Hh pathway activity has been demonstrated in some cholangiocarcinomas [25] and hepatocellular carcinomas [26][27][28]. We reported that clonal HSC lines derived from cirrhotic rat liver express mRNA for Hh ligands [29]. However, the significance of this finding is uncertain.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…9 Moreover, HSCs possess signaling pathways required for stem cell functions such as hedgehog and ␤-catenin-dependent Wnt signaling. 10,11 Similar to hematopoietic stem cells, quiescent HSCs are resistant against CD95-mediated apoptosis and proliferate in response to CD95 ligand. [12][13][14][15] Thus, there is growing evidence that stellate cells are stem/progenitor cells of the vertebrate liver.…”
Section: S Tellate Cells Reside Within the Perisinusoidal Space Ofmentioning
confidence: 99%